PEMANFAATAN Pseudomonas putida SEBAGAI BIOREMEDIATOR LIMBAH IKAN KOI (Cyprinus carpio L.) PADA SISTEM AKUAPONIK - Maharrani Pratiwi; Sri Andayani; M. Firdaus (Jurnal Perikanan Unram, 2021)
Indonesia is a fishery center that contributes significantly to international fish production. The amount of fish production can not be separated from the cultivation of both consumption fish and ornamental fish. One of the ornamental fish that has been developed and has become the main commodity for trading is koi fish, and it has even become a mainstay commodity in several areas including Sukabumi, Cianjur, and Blitar (Kursini, 2015). Therefore, it is necessary to do research on the effect of different administration of Pseudomonas putida on the survival of Koi fish. The method used in this research is the experimental method, which is then repeated 3 times each. The results of the test of the effect of giving Pseudomonas putida in this study resulted that the higher koi fish weight gain in the aquaponics system was 4.8±0.12%, while the lowest koi fish culture was 3.6±0.12%. while the average pH of koi fish in aquaponic systems is higher, namely 8.36. Meanwhile, in the lowest koi fish culture, the results are 8.25 and Phosphate that the average phosphate of koi fish in aquaponic systems is higher, which is 2, 58 mg/l, while the lowest koi fish culture yielded 1.11 mg/l which decreased and improved water quality.